Formation of Strategic Provinces on Maritime Borders: A Political Economy Analysis of Natuna-Anambas Proposal - Andana, Fery; Kartono, Kartono (Journal of Maritime Policy Science, 2025)
The Natuna and Anambas regions have a strategic position as a maritime border region that is a concern in the national agenda, including through designation as part of the National Strategic Project (PSN). However, the reality of local development shows high fiscal dependence on central transfers, weak local revenue, and vulnerability to global economic fluctuations. This study aims to assess the potential of the Natuna-Anambas Province formation in strengthening fiscal independence and improving local economic governance. Using an exploratory qualitative approach and fiscal policy analysis, this study utilizes secondary data from regional financial reports, BPS statistics, and a literature review related to fiscal decentralization and the resource curse. The results show that the regional revenue structure dominated by the General Allocation Fund (DAU) and Revenue Sharing Fund (DBH) makes Natuna and Anambas vulnerable to central policy changes and commodity price volatility. In addition, the benefits of PSN have not been fully distributed to local communities due to limited institutional capacity and lack of integration of local economic development. The establishment of a new province has the potential to be a solution if accompanied by strengthening fiscal governance, reforming DBH allocation, and economic diversification strategies. This article recommends a policy roadmap based on a multi-level governance approach to promote fiscal autonomy and inclusive and sustainable economic development.